THE EVOLUTION OF AL-JALĀLĪ CALENDAR: INSIGHTS FROM ‘UMAR KHAYYĀM'S CONTRIBUTIONS - Alpaten, Ulil Albab Al aulia; Harahap, Rustam Dahar Karnadi Apollo (Fakultas Syari'ah dan Hukum UIN Walisongo, 2024)
The Al-Jalālī calendar, developed by ‘Umar Khayyām in the 11th century, has important significance in Islamic history and culture. This study aims to trace the calendar's evolution, focusing on Khayyām's contributions and impact on the development of science and culture. The methods used include literature study, document analysis, and review of astronomical methods used by Khayyām. This journal highlights its scientific significance in the development of the calendar system, describing the journey of the Al-Jalālī Calendar from its initial concept to the improvements it obtained. An in-depth analysis of ‘Umar Khayyām's contributions and the development of the Al-Jalālī Calendar provides a rich insight into the history, mathematics, and astronomy of the time and its influence on time measurement and administration in Persian society.